2011
DOI: 10.1002/pssc.201001102
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and time dependent threshold voltage characterization of AlGaN/GaN high electron mobility transistors

Abstract: High electron mobility transistors (HEMTs) based on the AlGaN/GaN heterostructure were fabricated with treatments of either CF4 plasma or 19F+ implantation prior to gate deposition. The post‐treatment threshold voltage VT was shifted positively from ‐4.06 V to 0.25 V and ‐0.34 V, respectively. Subsequent 400 °C, up to 10 min furnace annealing increased the transconductance gm in both samples, leading to a two order of magnitude increase in drain current density. The implanted sample improved its VT to ‐0.16 V,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…7 the effect over temperature is made more visible. In correlation with the works on [11] for eGaN-FETs, it is found that the threshold voltage is increasing towards higher temperatures. However, this is only valid up to • C. Previous work showed a steady increase towards 120 • C where this particular device is showing a decreasing for temperatures larger than 100 • C. The reason for this drop is yet unclear, this may also be highly dependent on the chosen devices.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…7 the effect over temperature is made more visible. In correlation with the works on [11] for eGaN-FETs, it is found that the threshold voltage is increasing towards higher temperatures. However, this is only valid up to • C. Previous work showed a steady increase towards 120 • C where this particular device is showing a decreasing for temperatures larger than 100 • C. The reason for this drop is yet unclear, this may also be highly dependent on the chosen devices.…”
Section: Resultssupporting
confidence: 65%
“…The point at which this happens is expected to be impacted by temperature. A higher temperature in the device can lead to a higher threshold voltage as is shown by [11]. The measurement shown temperatures up to 120 • C but it is unclear if this trend will proceed with temperatures up to 225 • C.…”
Section: Impact Of Parasitics On Switching Behaviormentioning
confidence: 91%
“…14,15) However, previous reports demonstrated that the fluorine plasma treatment or ion implantation E-mode AlGaN/GaN HEMTs have poor V th reliability, which could be related to a large number of vacancies or damage produced during the ion bombardment process. [16][17][18] In addition to plasma treatment or ion implantation, thermal diffusion could be also an effective method to introduce fluorine ions into AlGaN to realize E-mode HEMTs, which can avoid the formation of vacancies and damage in the plasma treatment or ion implantation process. Fluoride generally cannot decompose under high temperature conditions and only sublimes, which brings challenges to the thermal diffusion of fluorine ions.…”
mentioning
confidence: 99%
“…F plasma treatments have been used to achieve a positive threshold voltage. [8][9][10][11][12][13][14][15] Many groups have reported the results of fluorine implantation with different process conditions but the fluorine concentration in the film was not well controlled, [16][17][18][19][20] and references therein. Fluorine ions have been demonstrated to deplete two-dimensional electron gas directly and a positive shift in the threshold voltage.…”
mentioning
confidence: 99%
“…Fluorine ions have been demonstrated to deplete two-dimensional electron gas directly and a positive shift in the threshold voltage. [8][9][10][11][12][13][14][15] But there lacks a physical model to describe how the immobile negative charges impacts on the device performance. Therefore, developing a physical model of effects the immobile negative charges on device performance is the aim of this paper.…”
mentioning
confidence: 99%